2007
DOI: 10.1038/emm.2007.78
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol inhibits production of nitric oxide and proinflammatory cytokines through MAPK signal transduction and NF-κB in LPS-stimulated BV-2 microglial cells

Abstract: Excessive production of nitric oxide (NO) and proinflammatory cytokines from activated microglia play an important role in human neurodegenerative disorders. Here, we investigated whether celastrol, which has been used as a potent anti-inflammatory and anti-oxidative agent in Chinese medicine, attenuates excessive production of NO and proinflammatory cytokines such as TNF-α and IL-1β in LPS-stimulated BV-2 cells, a mouse microglial cell line. We report here that the LPS-elicited excessive production of NO, TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 26 publications
1
66
1
1
Order By: Relevance
“…Celastrol affects several biological processes through the inhibition of ATF2, nuclear factor-KB, inducible NOS, VEGF receptors, HSP90, potassium/calcium channel and eventually increases the reactive oxygen species (ROS) in cancer cells, thus in turn activating apoptosis pathways. 16,22,[25][26][27][28][29] In the present study, we investigated whether ATF2 could contribute to primary and/or acquired drug resistance in NSCLC. We demonstrated that high expression levels of ATF2, at transcript and protein levels, are detected in NSCLC and ATF2 protein activation correlates with worse outcome in advanced NSCLC patients cisplatin-treated.…”
mentioning
confidence: 99%
“…Celastrol affects several biological processes through the inhibition of ATF2, nuclear factor-KB, inducible NOS, VEGF receptors, HSP90, potassium/calcium channel and eventually increases the reactive oxygen species (ROS) in cancer cells, thus in turn activating apoptosis pathways. 16,22,[25][26][27][28][29] In the present study, we investigated whether ATF2 could contribute to primary and/or acquired drug resistance in NSCLC. We demonstrated that high expression levels of ATF2, at transcript and protein levels, are detected in NSCLC and ATF2 protein activation correlates with worse outcome in advanced NSCLC patients cisplatin-treated.…”
mentioning
confidence: 99%
“…In recent years, celastrol has attracted attention due to its potential for use in anti-inflammation (Jung et al 2007;Kim et al 2009a, b;Pinna et al 2004), anti-tumor (Dai et al 2009;Ge et al 2010;He et al 2009a), and neuron degenerative disease amelioration applications (Allison et al 2001;Faust et al 2009;Kiaei et al 2005). Celastrol can inhibit NF-κB activation (He et al 2009a;Jung et al 2007; Lee et al 2006), arrest cell cycle (Ge et al 2010), and induce heat shock and anti-oxidant response (Faust et al 2009, Westerheide et al 2004. The most recent reports attribute these effects to an attack on the heat shock protein (HSP90) complex by celastrol (Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, after cells receive pathological stimuli, IκB protein is phosphorylated, a process leading to its ubiquitination and degradation. Consequently, released NF-κB translocates to the nucleus where it induces the expression of pro-inflammatory mediators (26). Using western blotting and immunofluorescence staining analyses, we found that GLGZD treatment significantly decreased the protein expression of TLR4 and MyD88, inhibited the phosphorylation of IκB and blocked the nuclear translocation of NF-κB in BV-2 cells, suggesting that GLGZD suppresses the activation of the TLR4/NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 91%